Kinetic and adsorption removal study of Malachite green dye on Carbon Nanotubes Immobilized Biomass (CNTIB) - Kabbashi, Nassereldeen Ahmed; Bello, Ibrahim; Alam, Md Zahangir; Mohamad Puad, Noor Illi; Nour, Abdurahman Hamid (AUCTORES Publishing LLC, 2018)
The adsorption of Malachite green (MG) onto Carbon Nanotubes Immobilized Biomass (CNTIB) was carried out in this research. The interactive effects of experimental variables such as Biosorbent loading, MG dye concentration and pH were investigated. Optimized conditions for adsorption studies were achieved by employing the Response Surface Methodology (RSM) of Design expert 7 software using the Faced Centered Central Composite Design (FCCD). MG adsorption uptake was found to increase with an increase in biosorbent loading. Isotherm studies showed that the experimental data better fitted with the Langmuir isotherm for CNTIB when compared to Freundlich isotherm. Adsorption kinetics was found to follow the pseudo-second order kinetic model which suggests that chemisorption is the process through which adsorption took place. The biosorbent was produced by immobilization technique. Optimized conditions of parameters for biosorption studies (initial dye concentration, biosorbent loading and pH) as well as response were determined. 111.0mg/L of dye was removed out of an initial dye concentration of 112.5mg/L. Acidic pH was favourable for the adsorption of MG. Coefficient of determination (R2) for biosorption model was 0.989. The biosorbent produced was characterized using SEM to determine its morphology and available functional groups which would further enhance its biosorption ability.